Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Petani Bawang Merah Pada Produk Pestisida Agricon di Kios Sumber Rejeki Kecamtan Tanjunganon Kabupaten Nganjuk - Kautsar Prastama; Masahid; Lilik Koesmihartono Putra; Deviana Diah Probowati (Oryza : Jurnal Agribisnis dan Pertanian Berkelanjutan, 2026)
This study aims to analyze the effect of the marketing mix (product, price, and promotion) on the purchasing decisions of shallot farmers toward Agricon pesticide products at Sumber Rejeki Agricultural Store, Tanjunganom District, Nganjuk Regency. This research used a quantitative approach with a sample of 60 respondents selected using purposive sampling. Data were collected through questionnaires, interviews, and documentation, then analyzed using multiple linear regression. The results show that product and promotion partially have a positive and significant effect on purchasing decisions, while price has a positive but not significant effect. Simultaneously, product, price, and promotion significantly affect purchasing decisions, with an Adjusted R Square of 0.490, meaning that 49.0 percent of the variation in purchasing decisions is explained by the three marketing mix variables. Product quality is found to be the most dominant factor influencing farmers' purchasing decisions, followed by promotion, while price is considered a secondary factor compared to pesticide effectiveness.